Effects of a maximal exercise test on neurocognitive function. Issue 6 (15th January 2007) - Covassin, Tracey; Weiss, Leigh; Powell, John; Womack, Christopher
Abstract : Objective: To examine the effects of a maximal exercise test on cognitive function in recreational athletes. Design: A repeated-measures design was used to compare baseline with post-cognitive function and fatigue symptoms after a maximal exercise test. Setting: Division 1 American Midwestern University, (Michigan State University, Michigan, USA). Participants: 102 male and female recreational athletes. Intervention: Participants in the experimental group (n = 54) were asked to perform a maximal treadmill exercise test to maximal oxygen uptake (VO2 max). Participants in the control group were asked to rest for 15 min. Main outcome measurements: All participants were administered a neuropsychological test battery called Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) before and after exercise to measure neurocognitive function and fatigue symptoms. Results: Results revealed a significant group (control, experimental)×time (baseline, post-test 1, post-test 2) interaction for verbal memory composite scores (p = 0.025). Specifically, verbal memory composite scores decreased in the experimental group from baseline to post-test 1 (p = 0.00). These values returned to baseline 3 days after the Vo 2 max test (p = 0.00). Further analysis on verbal memory composite scores demonstrated significant differences on immediate recall memory (p = 0.00) and delayed recall memory (p = 0.00). No significant differences were observed for visual memory (p = 0.54), motor processing speed (p = 0.68) and reaction time (p = 0.44) composite scores between the experimental and control groups. Conclusion: The results of this study suggest that a maximal exercise test attenuated a limiting effect on cognitive function. When utilising a neuropsychological test battery to evaluate a patient who has sustained a head injury, the test should not be administered immediately after a practice or a game session.